Measurement and Analysis of ground reaction forces Distribution and electromyography for Ankle Joint Fixation Injury Using Different Types of Shoes - Fakhri, Noora; Chiad , Jumaa S. (Al-Nahrain Journal for Engineering Sciences, 2024)
One of the health issues that many people encounter on a daily basis is bone fracture, which can happen for a number of reasons, such as arthritis, sprains, or external trauma . The patient experiences instability as a result of these issues . Internal fixation is a type of surgery used to support and mend a damaged bone Treatment options include ankle joint fixation, a surgical procedure employing pins, plates, rods, or screws. This study uses gait analysis methods to assess lower limb biomechanics . Gait analysis is vital for understanding walking patterns and intervention effectiveness. The impact of different shoe designs on ankle mechanics, using the finite element method and ANSYS, is investigated The results of the EMG and the GRF were discussed. This research deepens our understanding of lower limb biomechanics and ankle joint health. By evaluating stress effects and designing custom shoes, it enhances ankle injury treatment and management strategies. The patient, a 70-year-old woman with an internal fixation on her ankle joint, underwent a CT scan of her ankle. The patient underwent a number of experiments to evaluate her stability. EMG was used to determine the muscle stress for a brief period of time, and ground reaction force was then used to determine the pressure of walking. Both EMG and GRF have two walking speeds of1.5and 2 km/h while wearing four different types of shoes. The behavior of the EMG demonstrates that the stress on the muscle increases as walking speed increases, and the results varies depending on the shoe. The patient is afraid to apply pressure to the injured foot, so the health foot has better pressure over the entire foot